Identification of Spacial Pattern in Productive House of Pottery Craftsmen - Wardhani, Dyah Kusuma (Humaniora, 2016)
The research goals were to identify a spacial pattern in craftsmen house and to see its relevance to the social-cultural life of the craftsmen. The existence of domestic and economic activity in craftsmen house creates a spacial pattern with particular characteristics. Data were collected through direct observation, interviews, and visual documentation to record productive house, settlement condition, and sequences of pottery production. The in-depth interview focused on the use of time, space, and house modification in craftsmen house. House in the craftsmen settlement was growing gradually by adjusting to the inhabitant's needs. This research was included in qualitative research that described observation results and then analyzed spacial pattern formed in craftsmen house. Research results show that in this settlement beside the mixed, balanced, and separated type of productive house, there is also pottery collectors house type. The changes in the productive house are related to housing adaptation or house adjustment to accommodate production process. The settlement orientation is along the streets, but the existence of open space in the form of pottery kiln and hay storage become the main orientation for productive spaces inside the craftsmen house. Pottery kiln and hay storage have become open cultural space that characterizes the pottery craftsmen settlement.